2017
DOI: 10.1016/j.jacep.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Catheter Ablation of Atrial Fibrillation in 3,000 Consecutive Procedures

Abstract: The risk for CT in patients undergoing AF ablation at a single high-volume center was decreased with the use of balloon catheters. Extensive radiofrequency current ablation beyond PVI leads to an increased perforation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 24 publications
7
60
1
1
Order By: Relevance
“…Currently, cryoenergy is one of the most common technology in the catheter ablation of AF and cryoablation is an established procedure for PVI, particularly with the development of the second generation CB. Potential advantages of the CB include catheter adherence to tissue during ablation; homogeneous, circumferential, and durable ablation lesion; less risk of tamponade . However, the feasibility and safety of CB ablation for non‐PV sites, that is, LAA, and relevant technical data are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cryoenergy is one of the most common technology in the catheter ablation of AF and cryoablation is an established procedure for PVI, particularly with the development of the second generation CB. Potential advantages of the CB include catheter adherence to tissue during ablation; homogeneous, circumferential, and durable ablation lesion; less risk of tamponade . However, the feasibility and safety of CB ablation for non‐PV sites, that is, LAA, and relevant technical data are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complications were phrenic nerve palsy or vascular access injury. Chun et al 39 reported a statistically lower risk of tamponade among the cryoballoon PVI group than among the RF PVI group. This may in part be related to the requirement for only a single transseptal puncture to be performed, compared with two punctures, for more instances of RF PVI.…”
Section: S T Mathew and S S Pomentioning
confidence: 98%
“…The complication rate did not significantly differ in the RF and CB groups (respectively, 3.6% vs 2.2%; p=0.1). Chun et al [15] . have recently published the differential risk of cardiac tamponade in AF ablation procedures undertaken from May 2010 to July 2015 at a single center.…”
Section: Single Center Studies Comparing the Safety Of Cb Ablation Vsmentioning
confidence: 99%
“…A study has compared the incidence of pericardial effusion in a total of 133 consecutive patients undergoing ablation for paroxysmal AF (87 by RFA vs. 46 patients by CB-A) and no significant difference in the incidence of pericardial effusion between the cryoballoon and the RF groups were detected (11 vs. 16%) [26] . However, the incidence of cardiac tamponade has been reported to be higher following RFA [15]. A longer procedural time, coronary artery disease and arterial hypertension were found to be independent predictors of pericardial effusion during AF ablation [26] .…”
Section: Pericardial Effusion and Tamponadementioning
confidence: 99%